Analisa dan Perancangan Sistem Informasi Administrasi Kepegawaian Pada Dinas Kebudayaan dan Pariwisata Provinsi Kepulauan Bangka Belitung - Anisah Anisah; Nia Novianti (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2017)
Department of Culture and Tourism Bangka Belitung province is implementing elements of the government in the field of culture and tourism, handle by a Head Department . One of the units of work that there is a personnel department that handles staffing issues. At this time the data is processing system employee who applied the Department of Culture and Tourism Bangka Belitung province is already using a computer, using Microsoft Word and Microsoft Excel are stored in the folder, not to use a database (database) or not use the Database Management System (DBMS) as a place to save the data was related administrative personnel, so that the data is still standing on their own without the relationship between the data with others. So that why , in the preparation of reports and personnel administration the data takes a long time to search, because of it must be checked one by one every document was ouput. In order to find the data and preparing reports relating to personnel administration can be done quickly, a computerized information system needs to be applied to all issues relating to personnel administration can be resolved. So it takes the analysis and design of informationsystems personnel administration, which is in this case using object-oriented methodologies usesDiagram Unified Modelling Language (UML).